2012
DOI: 10.1007/s13311-012-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

Will Working Memory Training Generalize to Improve Off-Task Behavior in Children with Attention-Deficit/Hyperactivity Disorder?

Abstract: Computerized working memory and executive function training programs designed to target specific impairments in executive functioning are becoming increasingly available, yet how well these programs generalize to improve functional deficits in disorders, such as attentiondeficit/hyperactivity disorder (ADHD), beyond the training context is not well-established. The aim of this study was to examine the extent to which working memory (WM) training in children with ADHD would diminish a core dysfunctional behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 66 publications
6
130
4
1
Order By: Relevance
“…With regards to our results, such assessment should examine response control and WM in boys and girls with ADHD as different neurocognitive profiles may emerge. As for treatment implications, in line with prior work that has suggested the benefits of cognitive training to address neuropsychological deficits in children with ADHD (Chacko et al 2014; Gray et al 2012; Green et al 2012; Klingberg et al 2005), our results support the use of cognitive remediation training with a focus on systematically increasing WM demands in children with ADHD, and while preliminary and in need of replication, our results may suggest such training could be particularly important for girls with ADHD. However, it will be important to replicate our findings in future studies adequately powered to detect sex differences.…”
Section: Discussionsupporting
confidence: 88%
“…With regards to our results, such assessment should examine response control and WM in boys and girls with ADHD as different neurocognitive profiles may emerge. As for treatment implications, in line with prior work that has suggested the benefits of cognitive training to address neuropsychological deficits in children with ADHD (Chacko et al 2014; Gray et al 2012; Green et al 2012; Klingberg et al 2005), our results support the use of cognitive remediation training with a focus on systematically increasing WM demands in children with ADHD, and while preliminary and in need of replication, our results may suggest such training could be particularly important for girls with ADHD. However, it will be important to replicate our findings in future studies adequately powered to detect sex differences.…”
Section: Discussionsupporting
confidence: 88%
“…Another way of assessing effects in a more ecologically valid way is to assess classroom behavior as has been done in the study by Green and colleagues (Green et al 2012). This controlled WM training study included children with ADHD and had observers, who were blind to students' group belonging, rate students' behavior while performing an academic task (the Restricted Academic Setting Task).…”
Section: Transfer To Academic Performancementioning
confidence: 99%
“…Although a recent metaanalysis has suggested a lack of generalizable positive effect of computerized WM training (MelbyLervåg & Hulme, 2013), Green et al (2012) demonstrated that training in WM may impact off-task behavior. Future research can use the knowledge of cognition-academic relationships found here to target cognitive processes at optimal ages and predict academic impacts.…”
Section: Future Directionsmentioning
confidence: 99%